Algoritmo co-evolutivo para particionamento de dados e seleção de variáveis em problema de calibração multivariada. - Ramos, Jorcivan Silva (2015)
This paper presents the development of a co-evolutionary genetic algorithm for the selection of samples from a data set and the selection of variables from the samples selected in the context of multivariate calibration . Each sample is divided into the calibration set for the preparation of the model and validating the calibration set of model. The algorithm selects samples variables with the goal of building the calibration models. The results show that the data sets selected by the proposed algorithm models to produce better predictive ability of the models reported in the literature.